An engineered glove for investigating the neural correlates of finger movements using functional magnetic resonance imaging - Bonzano, Laura; Tacchino, Andrea; Roccatagliata, Luca; Inglese, Matilde; Mancardi, Giovanni L.; Novellino, Antonio; Bove, Marco (Frontiers in Human Neuroscience, 2015)
Objective measurement of concomitant finger motor performance is recommended for functional magnetic resonance imaging (fMRI) studies investigating brain activity during finger tapping tasks, because performance modality and ability can influence the selection of different neural networks. In this study, we present a novel glove system for quantitative evaluation of finger opposition movements during fMRI (called Glove Analyzer for fMRI - GAF). Several tests for MR compatibility were performed concerning magnet forces, image artifacts and right functioning of the system. Then, pilot fMRI of finger opposition tasks were conducted at 1.5T and 3T to investigate the neural correlates of sequences of finger opposition movements with the right hand, with simultaneous behavioral recording by means of GAF. All the MR compatibility tests succeeded, and the fMRI analysis revealed mainly the activation of the left sensorimotor areas and right cerebellum, regions that are known to be involved in finger movements. No artifactual clusters were detected in the activation maps. At the same time, through the parameters calculated by GAF it was possible to describe the sensorimotor strategy adopted by the subjects during the required task. Thus, the proposed device resulted to be MR compatible and can be useful for future fMRI studies investigating the neural correlates of finger opposition movements, allowing follow-up studies and comparisons among different groups of patients.